Triethylamine — A Versatile Organocatalyst in Organic Transformations: A Decade Update - Brahmachari, Goutam; Nayek, Nayana; Nurjamal, Khondekar; Karmakar, Indrajit; Begam, Sanchari (Synthesis, 2018)
Organocatalysts play pivotal roles in accomplishing a wide range of useful organic transformations, and organocatalytic reactions are now becoming powerful tools in the construction of simple to complex molecular scaffolds. This remarkable field is growing rapidly with new concepts and designs. During the recent past, triethylamine (or N,N-diethylethanamine), has emerged as an efficient organocatalyst in carrying out so many organic transformations, thereby producing interesting molecular frameworks. Triethylamine is relatively safe, commercially available and cheap. This review offers a decade update on the developments of triethylamine-catalyzed organic transformations reported during the period of 2008 through 2017.1 Introduction2 Organocatalytic Applications of Triethylamine in Organic Transformations2.1 Organic Transformations under Ambient Conditions2.2 Organic Transformations under Heating/Reflux Conditions3 Conclusion
Keywords: triethylamine; organocatalyst; catalytic applications; carbon–carbon bond; carbon–heteroatom bond; organic synthesis